Transcriptome analysis reveals the inhibitory nature of high nitrate during adventitious roots formation in the apple rootstock. Issue 3 (28th June 2021) - Zhang, Xiaoyun; Tahir, Muhammad Mobeen; Li, Shaohuan; Mao, Jiangping; Nawaz, Muhammad Azher; Liu, Yu; Li, Ke; Xing, Libo; Niu, Jianxin; Zhang, Dong
Abstract: In the process of vegetative propagation of apple rootstocks, the development of adventitious roots (ARs) has crucial importance. Nitrate is an essential nutrient necessary for plant growth; however, the inhibitory effect of high nitrate on ARs formation has not been explored. The physiological and molecular mechanisms underlying ARs inhibition were examined in this study. Stem cuttings of B9 apple rootstock were cultured on two nitrate treatments (T1 = 18.7 mM L −1 and T2 = 37.5 mM L −1 ), where T2 was identified as ARs inhibiting treatment. Morphological and anatomical observations advocating that high availability of nitrate inhibited AR formation by delaying the ARs initiation and emergence stages, where the root number was 287%, and the length was 604.6% lower than the T1 cuttings. Moreover, the contents of endogenous hormones were also elevated in response to T2 at most of the time points, which may cause a hormonal imbalance within the plant body and drive toward ARs inhibition. Furthermore, 3686 genes were differentially expressed by high‐throughput sequencing. Out of these, 1797 genes were upregulated, and 1889 genes were downregulated. Approximately 238 genes related to nitrate, hormones, root development, and cell‐cycle induction pathways were selected according to their potential to be involved in ARs regulation. This is the first study providing information regarding the inhibitory effect of high nitrate on ARs formation in apple rootstock.